Thin-Layer Drying Model and Antifungal Properties of Rubber Sheets Produced with Wood Vinegar as a Substitute for Formic and Acetic Acids - Wattana, Wassachol; Lakachaiworakun, Putipong; Rachsiriwatcharabul, Natworapol; Eakvanich, Visit; Dangwilailux, Panya; Kalasee, Wachara (My University, 2025)
Currently, workers in the ribbed smoked sheet (RSS) rubber production industry face increasing health risks, primarily due to their direct involvement in converting fresh latex into raw rubber sheets. This process involves the manual addition of appropriately diluted commercial formic acid and acetic acid to induce coagulation, resulting in a tofu-like consistency, which is subsequently processed into rubber sheets. Previous studies have indicated that the use of commercial formic and acetic acids poses significant health hazards to workers and contributes to environmental pollution. Therefore, this study explores the feasibility of replacing commercial formic and acetic acids with wood vinegar derived from para-rubber wood, bamboo, and eucalyptus in the RSS production process. Wood vinegar samples from the three biomass sources were analyzed for their organic compound compositions using gas chromatography and subsequently used as coagulants in the preparation of raw rubber sheets. The drying kinetics and antifungal properties of the resulting sheets were then evaluated. The results revealed that wood vinegar derived from para-rubber wood contained the highest concentration of acetic acid (41.34%), followed by bamboo (38.19%) and eucalyptus (31.25%). Rubber sheets coagulated with wood vinegar from para-rubber wood and bamboo exhibited drying kinetics comparable to those obtained using acetic acid, with the two-term exponential model providing the best fit. Conversely, rubber sheets coagulated with eucalyptus-derived wood vinegar, which had a relatively high concentration of phenolic derivatives (22.08%), followed drying behavior consistent with the Midilli et al. model, similar to sheets treated with formic acid. In terms of antifungal properties, five fungal genera—Aspergillus, Penicillium, Fusarium, Trichoderma, and Paecilomyces—were identified on the rubber sheets. Fungal growth was most pronounced in the control samples (untreated with wood vinegar), whereas samples treated with wood vinegar exhibited significantly reduced fungal colonization. These findings indicate that wood vinegar is effective in inhibiting fungal growth on the surface of rubber sheets and may serve as a safer and more environmentally friendly alternative to commercial acid coagulants.
Keywords: antifungal properties; drying kinetics; fourier-transform infrared spectroscopy (FTIR); ribbed smoked sheets (RSS); wood vinegar